Surface potential-governed cellular osteogenic differentiation on ferroelectric polyvinylidene fluoride trifluoroethylene films. (1st July 2018) - Tang, Bolin; Zhang, Bo; Zhuang, Junjun; Wang, Qi; Dong, Lingqing; Cheng, Kui; Weng, Wenjian
Graphical abstract: Abstract: Surface potential of biomaterials can dramatically influence cellular osteogenic differentiation. In this work, a wide range of surface potential on ferroelectric polyvinylidene fluoride trifluoroethylene (P(VDF-TrFE)) films was designed to get insight into the interfacial interaction of cell-charged surface. The P(VDF-TrFE) films poled by contact electric poling at various electric fields obtained well stabilized surface potential, with wide range from −3 to 915 mV. The osteogenic differentiation level of cells cultured on the films was strongly dependent on surface potential and reached the optimum at 391 mV in this system. Binding specificity assay indicated that surface potential could effectively govern the binding state of the adsorbed fibronectin (FN) with integrin. Molecular dynamic (MD) simulation further revealed that surface potential brought a significant difference in the relative distance between RGD and synergy PHSRN sites of adsorbed FN, resulting in a distinct integrin-FN binding state. These results suggest that the full binding of integrin α5β1 with both RGD and PHSRN sites of FN possesses a strong ability to activate osteogenic signaling pathway. This work sheds light on the underlying mechanism of osteogenic differentiation behavior on charged material surfaces, and also provides a guidance for designing a reasonable charged surface to enhance osteogenic differentiation. Statement of Significance: The ferroelectric P(VDF-TrFE) films with steady and a wide range of surface potential were designed to understand underlying mechanism of cell-charged surface interaction. The results showed that the charged surface well favored upregulation of osteogenic differentiation of MC3T3-E1 cells, and more importantly, a highest level occurred on the film with a moderate surface potential. Experiments and molecular dynamics simulation demonstrated that the surface potential could govern fibronectin conformation and then the integrin-fibronectin binding. We propose that a full binding state of integrin α5β1 with fibronectin induces effective activation of integrin-mediated FAK/ERK signaling pathway to upregulate cellular osteogenic differentiation. This work provides a guidance for designing a reasonable charged surface to enhance osteogenic differentiation.